Muslims' integration as a way to defuse the "Muslim Question": insights from the Swiss case - Gianni, Matteo (Critical research on religion, 2016)
The article argues that in European public debates the Muslim Question is performed by and linked to the issues of Muslims' integration and recognition as political (unthreatening) subjects. I suggest that, in order to defuse the performative negative effects of the Muslim Question on Muslims' democratic agency, we should address it without rendering them invisible in the public sphere and in enhancing their political agency. Drawing from an analysis of the Swiss case I show that integration because adjustment entails a depoliticization and a normalization of Muslims' political agency. In this way, integration as a process acts as an alternative and as a way to empower Muslim political subjectivity and therefore the fairest way to tackle the undemocratic impact of the Muslim Question.